2016
DOI: 10.1016/j.optom.2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Accommodation and pupil responses to random-dot stereograms

Abstract: We investigated the dynamics of accommodative and pupillary responses to random-dot stereograms presented in crossed and uncrossed disparity in six visually normal young adult subjects (mean age = 25.8 ± 3.1 years). Accommodation and pupil measures were monitored monocularly with a custom built photorefraction system while subjects fixated at the center of a random-dot stereogram. On each trial, the stereogram initially depicted a flat plane and then changed to depict a sinusoidal corrugation in depth while fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Usually, random-dot stimuli are used for stereoacuity assessment in clinical practice, but recent published works showed their application also in improving stereopsis values in amblyopia [ 16 , 54 ]. The use of a random-dot stereogram entails a cortical activation in the early visual cortex, particularly with mixed-polarity stimulus [ 61 ], and a small but significant activation of the pupil and accommodation responses [ 62 ]. Additionally, the optimal size of the dots should be considered for well-designed random-dot stimuli, since the literature suggests that larger dots implicate better stereo-perception [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Usually, random-dot stimuli are used for stereoacuity assessment in clinical practice, but recent published works showed their application also in improving stereopsis values in amblyopia [ 16 , 54 ]. The use of a random-dot stereogram entails a cortical activation in the early visual cortex, particularly with mixed-polarity stimulus [ 61 ], and a small but significant activation of the pupil and accommodation responses [ 62 ]. Additionally, the optimal size of the dots should be considered for well-designed random-dot stimuli, since the literature suggests that larger dots implicate better stereo-perception [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…This would improve the speed of vision screenings by performing the ST test at distance and assuming the absence of visual acuities poorer than 0.1 logMAR without conducting a visual acuity test. Myopic refractive errors could be easily detected with ST at distance even though hyperopia may go undetected because the subject might accommodate like with a visual acuity test (Suryakumar and Allison 2015). Hess et al, with a similar random dot stereotest, also reported a loss in stereopsis with the reduction in visual acuity (Hess et al 2016).…”
Section: Discussionmentioning
confidence: 99%